Colistin 투여 중 발생한 급성 신손상의 임상적 의의 - 남우진; Woo Jin Nam; 신정호; Jung Ho Shin; 한민지; Min Jee Han; 박윤수; Youn Su Park; 김수현; Su Hyun Kim; 오동진; Dong Jin Oh; et al. (Kidney research and clinical practice, 2011)
Purpose: Colistin (colistimethate sodium) became available for clinical use in 1959 and was used until the early 1980s to treat infections caused by Gram-negative rods. It was abandoned during the last two decades mainly due to its significant nephrotoxicity. However, the emergence of multidrug-resistant (MDR) bacteria such as Pseudomonas aeruginosa and Acinetobacter baumanii has resulted in significantly increased use of intravenous colistin. This study was designed to investigate the incidence and risk factors of acute kidney injury (AKI) associated with intravenous colistin (colistimethate sodium) treatment. Methods: We retrospectively collected the data from patients who were admitted to Chung-Ang University Hospital and treated with colistin from May 2007 to June 2009. Among these, we excluded the patients with baseline glomerular filtration rate (GFR) less than 15 ml/min/1.73m2. AKI was defined as an increase of creatinine more than 150% from the baseline, according to RIFLE criteria. Results: A total of 92 patients met the inclusion criteria and were included in the analysis. AKI occurred in 43 (47%) of the 92 patients. The cumulative doses (2.51±1.89 vs. 1.75±1.35 g, p=0.032) of colistin were significantly greater in the AKI group than in the normal kidney function (NKF) group. Serum creatinine level showed a significant increase in the AKI group, from day 3 (1.6±1.1 vs. 0.9±0.5 mg/dL, p=0.001) to day 90 (2.1±1.9 vs. 0.7±0.2 mg/dL, p=0.033). Furthermore, the occurrence of AKI at day 3 was a significant predictor of shorter survival (Log rank test p=0.031). Conclusion: AKI was a relatively common side effect of colistin. The cumulative dose was critical, rather than the daily dose or duration of treatment. Early acute kidney injury may predict shorter cumulative survival in patients undergoing colistin treatment.